Monitoring of panelera cane production using GIS and remote sensing tools, 2016-2017 years, Mérida, Venezuela - Guillén-García, Carlos Enrique (2019)
Currently, methodologies for evaluating agricultural production do not allow precision tracking or monitoring of the production. The state Merida in Venezuela contributes to the country with more than 515,000 MT in agricultural goods. Lack of the above mentioned methodologies hinder the truthful capture of agricultural production data; alternative technologies are being used to overcome such deficiency. Panelera cane (Saccharum officinarum sp) has been monitored through Sentinel 2A satellite images captured from 27/03/2016 to 01/04/2017; and processed with QGIS-2.18 software. Agrarian records were used to establish training and verification areas of the supervised classification 379 hectares (ha) of crop were identified by 27/03/2016; and 361 ha by 01/04/2017. The present evaluation identified 51.6% (129 ha) of additional area as that reported by the official institutions of Mérida for the year 2016; production is estimated to exceed by more than 50% in 2017 because institutions has not consolidated the information.